ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN ANEMIA PADA REMAJA PUTRI - Widya, Wastu; Yulianita, Yulianita; Anwar, Yulianti; Amanupunnyo, Notesya Astri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Anemia in Indonesia remains one of the public health issues that requires serious and sustained attention. Adolescent girls in puberty are at high risk of iron deficiency anemia. The purpose of this study was to identify factors associated with anemia in adolescent girls. A cross-sectional study design was used in this study. The study was conducted at a high school in the Kalampangan Community Health Center working area. The study was conducted in November 2024. The population consisted of female students at high schools in the Kalampangan Community Health Center working area. The sample consisted of 117 respondents. The sampling technique used was proportionate stratified random sampling. The research instrument used was a research questionnaire. Data analysis was performed using univariate and bivariate analysis. The results showed a relationship between iron tablet consumption compliance (p value: 0.000) and nutritional status (p value: 0.024) with the incidence of anemia in adolescents. It is recommended that the relevant health centers take further action, including developing intervention programs that cover education, support, and strategies to improve access to iron tablets at the school, family, and community levels. Keywords: Adolescents, Compliance, Nutritional Status